2015
DOI: 10.1155/2015/148769
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality among Adult Antiretroviral Therapy Users in Southeastern Ethiopia: Retrospective Cohort Study

Abstract: Background. Although efforts have been made to reduce AIDS-related mortality by providing antiretroviral therapy (ART) services, still people are dying while they are on treatment due to several factors. This study aimed to investigate the predictors of mortality among adult antiretroviral therapy (ART) users in Goba Hospital, Southeast Ethiopia. Methods. The medical records of 2036 ART users who enrolled at Goba Hospital between 2007 and 2012 were reviewed and sociodemographic, clinical, and ART-related data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
29
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 26 publications
11
29
3
Order By: Relevance
“…Although our study did not find any association between gender and the survival time until HIV/AIDS-related death, other studies in Ethiopia and abroad have reported that the mortality rate seems to be higher in males than in females [7,26]. Among possible reasons for the gender difference, it has been suggested that female patients tend to know about their HIV status at an earlier stage and begin antiretroviral therapy with better CD4 cell counts relative to males [7].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Although our study did not find any association between gender and the survival time until HIV/AIDS-related death, other studies in Ethiopia and abroad have reported that the mortality rate seems to be higher in males than in females [7,26]. Among possible reasons for the gender difference, it has been suggested that female patients tend to know about their HIV status at an earlier stage and begin antiretroviral therapy with better CD4 cell counts relative to males [7].…”
Section: Discussioncontrasting
confidence: 96%
“…High mortality rates during the first months after beginning the ART regimen were also reported through prospective cohort studies in Tanzania and South Africa [4,23], and were strongly associated with anaemia, thrombocytopenia, and severe malnutrition [4,23,24]. In Ethiopia, it was further found that early high death rates mainly occurred in patients with an advanced disease stage [25], as also reported in studies conducted in sub-Saharan Africa countries [26]. …”
Section: Discussionmentioning
confidence: 62%
“…In our cohort, the important determinants of death in the first six months were: having CD4 cell count below 100, having other AIDS defining conditions, not receiving cotrimoxazole, and being on treatment after 2010. These findings are in agreement with Setegn et al (24). The fact that mortality increased in the later years of treatment where quality of care is expected to be better is paradoxical and warrants further investigation.…”
Section: Discussionsupporting
confidence: 94%
“…Association of TB with mortality was demonstrated in studies by Setegn et al, Bane et al, and Aragie et al (21, 24, 25). Tuberculosis associated mortality typically coincided with peak periods of TB diagnosis.…”
Section: Discussionmentioning
confidence: 85%
“…Likewise, those bedridden clients at initiation of ART were more likely to die compared to working functional status clients. In this regard, studies from Ethiopia and Nepal reported supporting evidences that being bedridden was a predictor of mortality during ART care [11,21,26,27].…”
Section: Discussionmentioning
confidence: 88%